1969
DOI: 10.1139/y69-122
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines and cold thermogenesis in sheep

Abstract: Experiments were performed to assess the role of catecholamines in cold thermogenesis in warm- and cold-acclimated adult sheep. Urinary excretion of both noradrenaline and adrenaline increased in sheep exposed to cold. Propranolol (1 mg/kg) reduced cold thermogenesis in warm- and cold-acclimated sheep by 8% and 12% respectively. Noradrenaline and adrenaline infusions at 1 μg/kg min for 30 min had no significant effect on the rate of heat production of warm- or cold-acclimated sheep. Phenoxybenzamine (3.0 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
3
8
1
Order By: Relevance
“…Since Leduc (1961) reported that cold exposure increased the urinary excretion of catecholamines in rats, this observation has been confirmed by numerous other workers. The increased excretion of catecholamines reported herein confirms the results reported in rats (LeBlanc & Nadeau, 1961; Leduc, 1961;Motelica, 1969;Shum, Johnson & Flattery, 1969;Smith & Dugal, 1964), in man (Arnett & Watts, 1960;Suzuki, Tonoue, Matsuzaki & Yamamoto, 1967), in sheep (Webster, Heitman, Hays & Olynyk, 1969) and in cattle (Alvarez & Johnson, 1970). There was also an increase in heart rate in the sheep exposed to cold.…”
Section: Discussionsupporting
confidence: 89%
“…Since Leduc (1961) reported that cold exposure increased the urinary excretion of catecholamines in rats, this observation has been confirmed by numerous other workers. The increased excretion of catecholamines reported herein confirms the results reported in rats (LeBlanc & Nadeau, 1961; Leduc, 1961;Motelica, 1969;Shum, Johnson & Flattery, 1969;Smith & Dugal, 1964), in man (Arnett & Watts, 1960;Suzuki, Tonoue, Matsuzaki & Yamamoto, 1967), in sheep (Webster, Heitman, Hays & Olynyk, 1969) and in cattle (Alvarez & Johnson, 1970). There was also an increase in heart rate in the sheep exposed to cold.…”
Section: Discussionsupporting
confidence: 89%
“…The significant increase in whole-body oxygen consumption in response to cold is consistent with previous observations reported in the literature (Thompson et al 1975;Webster et al 1969). These authors showed that cold exposure caused at least a two-fold increase in metabolic activity, a change comparable with the response observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…These authors showed that cold exposure caused at least a two-fold increase in metabolic activity, a change comparable with the response observed in the present study. In the present study, propranolol slightly, but not significantly, blocked the cold-induced increase in oxygen consumption, whereas in the study of Webster et al (1969), propranolol caused a significant decrease in heat production of sheep exposed to a severe cold stress (-30°C). The lack of significant change in response to the nonselective blocker in the present study could be explained in part by the less severe conditions used, i.e.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations